2014
DOI: 10.1210/me.2014-1006
|View full text |Cite
|
Sign up to set email alerts
|

Research Resource: EPSLiM: Ensemble Predictor for Short Linear Motifs in Nuclear Hormone Receptors

Abstract: Nuclear receptors (NRs) are a superfamily of transcription factors central to regulating many biological processes, including cell growth, death, metabolism, and immune responses. NR-mediated gene expression can be modulated by coactivators and corepressors through direct physical interaction or protein complexes with functional domains in NRs. One class of these domains includes short linear motifs (SLiMs), which facilitate protein-protein interactions, phosphorylation, and ligand binding primarily in the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…To assess the extent of structural disorderliness, the mimicry proteins were divided in three different categories based on the PDR, as was also done in earlier studies [ 26 , 27 , 41 ]. Our results revealed that 107 of the 147 bacterial (73%) and 16 of the 34 (47%) viral mimicry proteins were ordered (PDR <10%).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the extent of structural disorderliness, the mimicry proteins were divided in three different categories based on the PDR, as was also done in earlier studies [ 26 , 27 , 41 ]. Our results revealed that 107 of the 147 bacterial (73%) and 16 of the 34 (47%) viral mimicry proteins were ordered (PDR <10%).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the ability to be involved in such protein-protein interactions allows the BAG domain of Bag-1L to exert a great impact on AR function. Since several steroid receptors have SLiMs-containing regions at their intrinsically disordered N-termini [97], it seems plausible that they could also be targeted by the BAG domain of Bag-1L. It is likely that they already account for the reported effects of Bag-1L on steroid receptor action [8183].…”
Section: Nuclear Action Of Bag-1mentioning
confidence: 99%
“…They find that a slowly exchanging Kapb1 phase forms a key constituent with the FG Nups that exists simultaneously in a fast phase, and that this suggests a Kapcentric barrier mechanism. 52 53 A rapid lysine ubiquitination predictor called Rapid UBIquitination (RUBI) was released by Walsh et al 54 In training RUBI, they found that intrinsic disorder was weakly anti-correlated with ubiquitination. The online protein characterization tool cleverSuite was introduced by Klus et al CleverSuite reports statistics on protein sequences based on their physico-chemical properties.…”
mentioning
confidence: 99%